Optimizing resources for sustainable maize production under different intercrop association in eastern sub Himalayan region of India - Harkesh Meena; Partha Sarathi Patra; Pabitra Adhikary; Arju Sahid Ahmed; Shyamal Kheroar; Shovik Deb; Feroze Hasan Rahman; Amrit Tamang; Bimal Das; Pijush Somondal (Frontiers in Sustainable Food Systems)
Intercropping is a sustainable agricultural approach that plays a crucial role in improving land use efficiency, enhancing soil fertility and boosting overall crop productivity. In the eastern sub Himalayan region of West Bengal, India, this practice holds significant promise for transforming traditional farming by optimizing yield per unit area while promoting environmental sustainability. Maize (Zea mays L.), a highly adaptable crop that serves as a staple food and animal feed, can benefit substantially from intercropping with legumes and non-legumes. However, systematic evaluations of maize-based intercropping systems in this region remain limited. This study was conducted to assess the comparative performance of four maize based intercropping systems namely maize-mustard, maize-lentil, maize-wheat and maize-pea conducted during the rabi seasons of 2021–22 and 2023–24. The hypothesis posited that intercropping with legumes would significantly enhance maize productivity. The experiment followed a Randomized Block Design (RBD) with four replications and key parameters such as growth traits, yield components, weed control, nutrient uptake, changes in soil chemical properties and economic outcomes were measured. Sole maize plots recorded superior growth and yield attributes, producing the highest grain yields. However, the maize + pea intercropping system markedly outperformed in terms of overall system productivity, increasing yield by 62.31 and 68.84% over sole maize in the first and second years, respectively. Legume-based systems not only contributed to better weed suppression but also enhanced soil fertility. The economic analysis revealed that the maize + pea system delivered the highest additional net returns of ₹92,441 and ₹1,12,775 ha−1 in the first and second years compared to sole maize. The results clearly demonstrate the advantages of intercropping maize, especially with pea, under rabi conditions in the eastern sub-Himalayan region. This strategy significantly boosts productivity, improves resource use efficiency and maximizes economic benefits. These findings provide critical insights into sustainable crop management and can serve as a model for other regions with similar agro-ecological conditions. The study strongly advocates for the integration of legumes in maize intercropping systems, highlighting their potential to address the twin challenges of food security and environmental sustainability.